Identifikasi Potensi Air Tanah Berdasarkan Metode Geolistrik Resistivitas dan Survei Hidrogeologi (Studi Kasus Dusun Sumber Waluh, Desa Pringgodani, Kec. Bantur, Kabupaten Malang) - Susilo, Adi; Juwono, Alamsyah M.; Aprilia, Faridha; Idmi, Mohammad Habibiy; Hisyam, Farizky; Hasan, Muhammad Fathur Rouf (Universitas Sultan Ageng Tirtayasa, 2025)
Bantur District in Malang Regency is an area that is vulnerable to drought disasters. A geoelectrical resistivity survey has been conducted in Sumber Waluh Hamlet, Pringgodani Village, Bantur District, Malang Regency as an effort to mitigate drought disasters. This study aims to identify the distribution of aquifer layers based on the results of subsurface resistivity modeling. The identified aquifer layers can be used as a solution to the problem of drought disasters. In this study, geoelectrical resistivity measurements used the VES technique, i.e. the Schlumberger configuration, which was carried out at seven points. Analysis of the modeling results showed the existence of a shallow aquifer layer with a depth of 8-20 meters and a deep aquifer with a depth range of 50-70 meters. The aquifer layer has a resistivity value between 0.51-31.36 Ωm which is interpreted as a tuffaceous sandstone layer. In hydrogeological modeling, it is interpreted that the position of the groundwater level is at a depth of 40-50 meters. Thus, the results of this study can be used as a recommendation for drilling points to find new water sources in the research area.